Case Report: Subcutaneous ofatumumab for patients with immunosuppressant-dependent or ineffective primary membranous nephropathy - Chen, Jie; Li, De-tian; Feng, Xin; Zhang, Bei-Ru (Frontiers in Immunology, 2025)
CD20 monoclonal antibodies (mAbs), particularly rituximab, have become a preferred treatment for many patients with phospholipase A2 receptor (PLA2R)-related membranous nephropathy (MN). However, some patients either fail to respond to rituximab or experience adverse reactions, indicating that newer-generation CD20 mAbs may offer a more effective alternative. Recently, subcutaneous ofatumumab has been utilized in the treatment of relapsing multiple sclerosis (RMS). This study presents two patients of primary membranous nephropathy (PMN) patients who were treated with subcutaneous ofatumumab. One patient was unresponsive to immunosuppressive therapies, while the other experienced recurrence after drug withdrawal. After ofatumumab therapy, Case 1 achieved PLA2R antibody negativity, and Case 2 showed improvements in renal function and hypoproteinemia. Both cases experienced a reduction in proteinuria. No adverse reactions were reported during the observation period. In conclusion, this study highlights the efficacy and safety of subcutaneous ofatumumab in treating PMN, particularly in patients who have failed or relapsed after conventional therapies.